Antioxidant Activity and Vitamin C Concentration Analysis of Gandaria (Bouae macrophylla Griff) Ethanol Extract Using Spectrophotometry UV Vis - Eva Kholifah; Dewi Nurazizah; Fajrin Noviyanto (Universitas Muhammadiyah Yogyakarta, 2023)
Antioxidants are chemical compounds that donate one or more electrons to free radicals to inhibit free radical reactions. One of the potential antioxidant sources is gandaria fruit (Bouea Macrophylla Griff). This research aims to determine the antioxidant activity and vitamin C content of the gandaria fruit extract. Gandaria fruit was macerated with ethanol as a solvent. Furthermore, the rotated extract was carried out for the phytochemical screening. The results of the phytochemical screening of the gandaria fruit extract showed a positive of flavonoids, terpenoids, tannins, saponins, and phenolics. The gandaria fruit extract was tested for antioxidants and quantitative analysis of vitamin C levels to obtain IC50 values and vitamin C levels using spectrophotometry UV-Vis at a wavelength of 517nm with vitamin C as a positive control. The results of spectrophotometric measurements revealed that the gandaria fruit extract had an IC50 value of 5.72 g/ml, and vitamin C had an IC50 value of 2.260 g/ml, indicating that the gandaria fruit extract and vitamin C had very strong antioxidants. The value of vitamin C levels was 0.526 mg.